منهج التصحيح والتضعيف عند المحدثين: دراسة نقدية لمنهج الشيخ الألباني نموذجا - Muhammad Khairul Mustaghfirin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
The research aims to stand on the method of judging the hadith on the validity, goodness, weakness, or condition of the narrators, and to identify the origins of the hadith imams, past and present, in correcting and weakening according to certain standards and scientific standards that are subject to the law of the novel, the origins of hadith and its sciences, wound and modification. It also aims to study Sheikh Al-Albani’s approach to correction and weakening. Objective scientific critical study, in this research, the researcher pursued an objective analytical and critical approach. It also relies on the study of hadith books, their collections, and abundant encyclopedias. It is based on the aspect of hadith sciences, in a sufficiently library method, so that it is based on the study of references and available sources specialized in the subject in question, and the most important findings of the researcher through research and reading of this. The matter is that judging a hadith is a matter of discretion, so it is the case of a mujtahid in jurisprudential rulings that he is right and wrong.